Return On Asset, Intensitas Modal, Tax Avoidance: Corporate Governance Sebagai Variabel Moderasi - Ahmad Ghozali (Jurnal Literasi Akuntansi, 2021)
Purpose: This study aims to examine whether return on assets and capital intensity can influencepractices tax avoidance and be moderated by corporate governance. Method: The sample uses manufacturing sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. The sample selection used pruprosive sampling technique so that 52 companies and 220 financial statements were obtained. Testing the sample using multiple linear regression analysis and absolute difference value test to test the moderating variable using the SPSS 20 analysis tool. Finding: The variable return on assets has a positive effect on tax avoidance practices but capital intensity has no effect on tax avoidance. Corporate governance can moderate the positif effect of return on assets on tax avoidance but is unable to moderate the relationship between capital intensity and tax avoidance. Novelty: This research is more interesting to do with the existence of corporate governance as a moderating variable that will strengthen or weaken the relationship between return on assets and capital intensity on tax avoidance.